Investigando a qualidade das refatorações de code smells em projetos java - Nascimento, João Teixeira do (2025)
Code smells are possible irregularities in the code that decrease its quality and worsen the maintainability of the software. The existence of code smells does not directly affect the functioning of the system, but it makes future modifications difficult. This paper presents an experience report on teaching code smells and code refactoring to a class of 42 software maintenance students in the semester of 2023.1, at the campus of the Federal University of Ceará in Russas. We analyzed the following points in the study: (i) the quality of the refactorings proposed by the participants, (ii) the difficulties and challenges faced in the code smell refactoring activity, (iii) the skills and benefits acquired at the end of the refactoring practice, (iv) the quality of the internal quality attributes of the systems after the refactorings and (v) the code smells and refactoring techniques most used during the study. We found that: (i) half of the refactorings in the study proved to be of good quality, (ii) code smells that affected a large amount of code proved to be more difficult to refactor, (iii) participants indicated that they gained good analytical skills, (iv) systems that received good refactorings showed significant improvements in quality, and (v) participants understood which techniques they needed to use to refactor the code smells that existed in their systems.